Jawabanmu

2014-09-11T19:45:40+07:00
X1=2x2

x1+x2+x3 = -b/a =8
2x2+x2+x3=8
3x2+x3=8 ......x3 = 8 - 3x2.  (1)

x1 . x2 + x2 . x3 + x3 . x1 = c/a =9

2 (x2)^2 + x2 . x3 + x3  . 2x2 = 9 ... (2)
2 (x2)^2 +  3x2 (8 - 3x2) = 9
2(x2)^2 + 24 x2 - 9 (x2)^2 -9 =0

7 (x2)^2 -24 x2 +9 =0

(7x2 -3)(x2-3)=0 .....x2 = 3/7  dan x2=3
                                                    x3=8 -3 .3 = - 1
                                                      x1=2x2= 4

x1 . x2. x3  = -d/a  = -m = 4 . 3 . (-1) =- 12